Penilaian Autentik pada Pembelajaran Pendidikan Agama Islam di SMP Negeri 4 Pematangsiantar - Muhammad Tamrin; Rahmat Rifai Lubis; Ahmad Aufa; Syaqila Adnanda Harahap (STAI Serdang Lubuk Pakam, 2021)
Assessments are often unable to assess what is really meant to be graded, even it seems that it is just giving a score. In fact, a real assessment is needed according to the results shown by students. This study aims to analyze the planning and implementation of authentic assessments as well as the obstacles faced in Islamic religious learning at SMP Negeri 4 Pematangsiantar. The study used a qualitative descriptive study, collecting data through observation, interviews, and documentation. Data analysis techniques through data reduction, data presentation and drawing conclusions. The results of the study explain that the planning of authentic assessment is done by first compiling an instrument based on the learning objectives that have been set, but in this case the teacher only modifies the instrument that has been approved by the curriculum development team of the city education office. Implementation is carried out by applying performance learning such as fardhu kifyah practice, ability tests in the form of non-tests, or observation sheets. Some of the obstacles faced by the large number of students who want to be assessed, personal value bias, difficulty in scoring management. The point is that authentic assessment is in accordance with the characteristics of Islamic education learning which does require performance-based or practice-based assessments.